The use of electrical resistivity measurement to estimate compressive strength in precast concrete processes (LACCEI, 2024)
In a precast concrete process, it is common to verify that the precast element has the necessary strength, for prestress release or demoulding, by testing concrete cylinders cured at equivalent conditions. This technique requires a considerable number of work hours, what makes the process inefficient. Considering that concrete electrical conductivity measurements can be used to estimate the pore structure of concrete, this study proposes the use of this technique to estimate concrete compressive strength, analysing its application with variable temperature. The use of non-destructive testing methods, as a suitable substitute of traditional techniques, considerably simplifies and modernizes the industrial process. This paper presents preliminary tests aimed at obtaining correlation graphs between concrete compressive strength and electrical conductivity, considering factory conditions. The correlation is good, but it is important to use correction factors to consider the shape and size of the element and the temperature of measurement. Moreover, the percolation condition of water must be high enough to obtain comparable results.